The Performance of Public Information and Documentation Management Officers in Electoral Information Services: A Case Study of the Gorontalo City Election Commission Following the 2024 Simultaneous Elections - Muhamad Maulid; Sastro Mustapa Wantu; Sri Yulianty Mozin (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the performance of Public Information and Documentation Management Officers (PPID) in electoral information services at the Gorontalo City Election Commission following the 2024 simultaneous elections. The study responds to the need to ensure transparent, accessible, and responsive public information services in local electoral institutions, particularly after a high-intensity electoral period that increased public demand for accurate election-related information. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation study, and analyzed through four dimensions of public service performance: effectiveness, efficiency, service quality, and responsiveness. The findings show that PPID performance was generally adequate. In terms of effectiveness, services were supported by a front office, digital applications, and dashboards, and the information provided was largely relevant to applicants’ requests, although more structured explanations and presentation were still required. In terms of efficiency, the use of softcopy documents, free-of-charge services, WhatsApp, e-PPID, and task distribution helped reduce service costs and time, but the disposition flow and internal coordination needed strengthening. Service quality was supported by the “KPU Melayani” principle, service declarations, standard operating procedures, suggestion boxes, and community satisfaction surveys; however, improvements were needed in clarity, completeness, accuracy, and comprehensibility of information. Responsiveness was reflected in direct services, email, WhatsApp, inter-subdivision coordination, objection mechanisms, and public consultation forums, although follow-up speed and digital channel optimization remained limited. The study concludes that strengthening coordination, information structuring, and digital service management is essential to improve electoral information transparency.